Syringolymphoid hyperplasia and follicular mucinosis in a patient with cutaneous T-cell lymphoma - Tannous, Zeina (1999)
Syringolymphoid hyperplasia with alopecia is an uncommon chronic dermatosis of which 9 cases have been reported, with or without follicular mucinosis or cutaneous T-cell lymphoma. We report a patient with cutaneous T-cell lymphoma and syringolymphoid hyperplasia and follicular mucinosis and review the previously reported cases. All reported cases with syringolymphoid hyperplasia were men (10 of 10), with the clinical findings of alopecia (9 of 10) and anhidrosis (3 of 10). Only 3 of 10 cases had associated follicular mucinosis. Of the 7 cases investigated, 6 were found to hve cutaneous T-cell lymphoma. Three patients were not investigated for cutaneous T-cell lymphoma. Although syringolymphoid hyperplasia can be idiopathic, it can also reflect a syringotropic cutaneous T-cell lymphoma. Careful follow-up with a biopsy of persistent lesions is recommended to evaluate for the presence of lymphoma. (J Am Acad Dermatol 1999;41:303-8.) Syringolymphoid hyperplasia (SLH) with alopecia is an uncommon chronic dermatosis first described by Sarkany et al in 1969.1 SLH is characterized histologically by hyperplasia of eccrine ducts and glands that are infiltrated and surrounded by a dense lymphocytic infiltrate. Nine patients with SLH have been reported with or without follicular mucinosis or cutaneous T-cell lymphoma (CTCL). We report a patient with CTCL and associated SLH and follicular mucinosis.